Circular Management of Tree Pruning Waste in City Park Management (Case Study in South Surabaya) - Albukhori, Azizah; Haryanta, Dwi; Sa'adah, Tatuk Tojibatus (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
This study aims to describe in depth the flow and management of circular tree pruning waste management to the management of urban parks in South Surabaya. This study uses a type of descriptive research with a qualitative approach. This research was conducted for six months from January to July 2024 and the research location focused on South Surabaya city parks and green lanes along Jl. A. Yani to Jl. Raya Darmo which are included in the South Surabaya area. Primary and secondary data sources. Data collection methods by interviews, documentation and observation. Data analysis uses triangulation analysis. The results of the study show that the management of city parks and green paths in South Surabaya produces tree pruning waste that is used as compost and distributed to city parks and green paths. The management of composting waste is an activity that aims to reduce organic waste and create environmentally friendly circular management. This management management strategy results in a good Green Open Space with fresh and green plants. Circular management activities provide benefits for city parks and green lanes in South Surabaya.